INTERNET OF THINGS: ITS EMERGENCE, CONCEPT AND SERVICES (World Economics and Finance Bulletin, 2023)
In present days, one can observe the penetration of digital technologies in both business and everyday life. This trend opens up new opportunities for individual companies and entire industries. This digital transformation allows companies to more accurately predict changes in the market and make decisions based on collected, processed and analyzed information about the various components of entrepreneurial activity. One of the incarnations of digital transformation is the concept of the Internet of things. This article discusses the concept of IoT, factors that contributed to its emergence, its services and a well-defined architecture for its deployment.
Keywords: Internet of Things; technology; data